P36. Dosimetric impact of treatment couch modelling and contention in pulmonary stereotactic treatment. (December 2016) - Mazoyer, F.; Gonod, M.; Petitfils, A.; Bidault, F.; Naudy, S.
Abstract : Introduction: During a treatment of lung lesion in stereotactic condition, for greater reproducibility, patients are immobilized with a complex and customized contention. The objective of this study is to determine the dosimetric impact of contention used in CGFL with the treatment couch. Materials and methods: Pulmonary stereotactic contentions used at CGFL are customizable vacuum cushions (BlueBAG™ BodyFIX). Ten treatment plans was performed without contention and couch. Each uses an arrangement of non modulated beams of 6 MV. Dose distributions of the resulting plans were re-calculated with the obtained Monitor Units, but with including of BlueBAG and treatment couch ("Exact IGRT" of Varian). Hounsfield Units used for internal structure couch are −945 and −300 for external structure. All dose distributions were calculated with Acuros XB V.11 (Varian Medical System). Results: New dose calculation with treatment couch and contention indicate a deterioration of around 1.9% of the D98% . Note that in 9 of the 10 case of the study, this D98% remains above the prescribe dose. The volume PTV receiving a dose is reduced by 1.6%. The most significant degradation was observed on the D50% and is 2.5% on average. Conclusions: Dosimetric impact of treatment couch modelling and contention in pulmonary stereotactic treatment is moderate. Although a significant deterioration of the dosimetric index was observed, coverage of prescribed dose remains acceptable.